Vietnam secondary education sector assessment, strategy and road map. (Country sector and thematic assessments., 2020)
The report reviews sector achievements and challenges as well as the Government of Viet Nam strategy and policies. It also outlines how the Asian Development Bank and other development partners have contributed to the sector. The report provides recommendations on measures to boost access to secondary education and to improve its overall quality and management.